Вдосконалення обладнання для заморожування харчових продуктів - Тарасенко, Віра Григорівна; Тарасенко, Вера Григорьевна; Tarasenko, Vira (My University, 2019)
UK: Стаття присвячена вдосконаленню пристроїв імпульсного заморожування харчових продуктів шляхом спрощення та зміни конструкції, зменшення втрат енергії, підвищення інтенсивності процесу заморожування, підвищення градієнту від’ємних температур. Розглянуто переваги перспективних способів заморожування, при яких істотно змінюються кінетика заморожування та теплофізичні характеристики харчових продуктів. RU: Статья посвящена усовершенствованию устройств импульсного замораживания пищевых продуктов путем упрощения и изменения конструкции, уменьшения потерь энергии, повышения интенсивности процесса замораживания, повышения градиента отрицательных температур. Рассмотрены преимущества перспективных способов замораживания, при которых существенно изменяются кинетика замораживания и теплофизические характеристики пищевых продуктов. EN: Device for impulse freezing of food products. Field of application: refrigeration equipment, namely, the design of devices used in the freezing of food products. As a result of the improvement, the design is simplified, energy losses are reduced and the intensity of the freezing process increases. The device for rapid freezing of food products containing a heat-insulated chilling chamber with a hydrophobic coating conveyor over which a superheated air supply pipe and a moisture separator are located is located outside the compressor to provide a refrigerant heat exchanger which is in thermal contact with the evaporator of the refrigerator. Device for fast freezing of food products. Field of application: meat, dairy, fish, fruit and vegetable and other branches of the food industry, where the use of freezing. In the device for quick freezing of food products containing a heat-insulated chilling chamber, a hydrophobic conveyor, a conduit for supplying supercooled air, a heat exchanger-cooler, a refrigerant evaporator, a receiver, a thermostatic valve, a water separator, a compressor, to a conduit for supplying supercooled air coupled a group of vortex nozzles with the Ranque-Hilsch effect. Technical result: the freezing of food is reduced during processing, stored separately and intact frumenty food, reduced leakage and damage cell juice during the phase transition, better freezing properties used refrigerant, increases the intensity of the process of freezing.
Усовершенствование оборудования для замораживания пищевых продуктов
Improvement of equipment for food products freezing
Keywords: швидке заморожування; вдосконалення; імпульсне заморожування; ефект Ранка-Хільша; вихровий ефект